Emergence of letermovir resistance in solid organ transplant recipients with ganciclovir resistant cytomegalovirus infection: A case series and review of the literature. Issue 3 (6th December 2020) - Hofmann, Eveline; Sidler, Daniel; Dahdal, Suzan; Bittel, Pascal; Suter‐Riniker, Franziska; Manuel, Oriol; Walti, Laura N.; Hirzel, Cédric
Abstract: Ganciclovir (GCV)‐resistant cytomegalovirus (CMV) infection is a common problem among solid organ transplant (SOT) recipients without prior CMV immunity (CMV D+/R−). GCV‐resistant CMV represents a particular challenge for CMV management. Letermovir is a recently licensed antiviral agent for primary CMV prophylaxis in allogenic hematopoietic stem cell transplant (HSCT) recipients. Given the favorable safety profile and its oral bioavailability letermovir may be considered a valuable off‐label option for secondary prophylaxis of GCV‐resistant CMV in SOT recipients. Here, we describe our experience with letermovir as secondary prophylaxis for GCV‐resistant CMV in two renal transplant recipients and review the literature in regard of previously published cases. Letermovir resistance emerged after a few months of secondary prophylaxis in the two renal transplant recipients. In both cases, the previously described UL56 C325Y letermovir resistance mutation was detected. In vitro studies of letermovir suggest a relatively low genetic barrier to resistance. Therefore, caution is warranted when using letermovir as secondary prophylaxis for GCV‐resistant CMV infection.